An Effect of Budget Participation and Information Asymetries Budgetary Slack Study at PT. Alfa Scorpio Gatot Subroto Medan - Rut Masidas Sibarani; Mika Debora Br Barus; Puja Rizqy Ramadhan (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of budgetary participation on budgetary slack, the effect of information asymmetry on budgetary slack, the effect of budgetary participation and information asymmetry on budgetary slack at PT. ALFA SCORPII GATOT SUBROTO MEDAN. The object of research is the manager and staff of 32 people who are involved in budget preparation. The data collection method in this study used a questionnaire. The analysis technique used is multiple linear regression. The results of this study indicate that based on the results of the F test, it is known that budgetary participation and information asymmetry simultaneously have a significant effect on budgetary slack. Budget participation has a significant effect on budgetary slack. Information asymmetry has a significant effect on budgetary slack.